Prophylactic dialysis improves short-term clinical outcome in patients with non-dialysis-dependent chronic kidney disease undergoing cardiac surgery: a meta-analysis of randomized controlled trials. Issue 1 (26th July 2021) - An, Xiuping; Ye, Nan; Bian, Weijing; Cheng, Hong
Abstract : Background: Several studies have reported that prophylactic dialysis can reduce the mortality of non-dialysis-dependent chronic kidney disease (CKD) patients after cardiac surgery. However, the results of complications in these randomized controlled trials (RCTs) were not consistent. We aimed to perform a meta-analysis to systematically evaluate the effect of prophylactic dialysis in these non-dialysis-dependent CKD patients. Methods: We systematically searched Medline, Embase, Cochrane's Library and other online sources for related RCTs. Effects of prophylactic dialysis on the incidence of 30 days' mortality and postoperative complications were analyzed. Results: Four RCTs comprising 395 patients were included, all of them treated by coronary artery bypass grafting. Treatment of preoperative and intraoperative prophylactic dialysis significantly reduced the rate of 30-day all-cause mortality (risk ratio [RR]: 0.27, 95% confidence interval [CI], 0.13–0.58, P < 0.001, I 2 = 0%) and the incidence of pulmonary complications (RR: 0.39, 95% CI, 0.20–0.77, P = 0.007, I 2 = 0%), low cardiac output (RR: 0.29, 95% CI, 0.09–0.99, P = 0.05, I 2 = 0%), and acute kidney injury (RR: 0.19, 95% CI: 0.07–0.52, P = 0.001, I 2 = 0%). However, there were no statistically significant differences between the dialysis group and the control group in gastrointestinal bleeding, sepsis or multiple organ failure, wound infection, arrhythmia, transient neurologic deficit, stroke and re-exploration for bleeding. Conclusion: Prophylactic dialysis can improve the 30-day clinical outcomes of non-dialysis-dependent CKD patients undergoing cardiac surgery, it was associated with the 30-day mortality benefit and led to a decrease in the incidence of pulmonary complications, as well as low cardiac output, and acute kidney injury.